1988
DOI: 10.1002/jnr.490200104
|View full text |Cite
|
Sign up to set email alerts
|

Expression of myelin protein genes in quaking mouse brain

Abstract: The expression of myelin proteins in actively myelinating quaking and control brains was studied. RNA was extracted from the brains of 18- and 27-day-old mice and analyzed by northern blot using cDNA probes for proteolipid protein (PLP), basic protein (BP), and myelin-associated glycoprotein (MAG). Two PLP transcripts of 3.2 and 2.4 kb (kilobase) were found, whereas PB and MAG probes hybridized to single regions of 2.2 and 2.5 kb, respectively. No abnormality in the transcript pattern was detectable in the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…We surmise that the Northern blot analyses of Fujita et al [21] were insufficiently sensitive to detect both isoforms since they even failed to detect L-MAG in normal adult mice. It is also worth noting that Konat et al [2] have, by Northern blot analysis of mRNA for qk MAG, concluded that the processing of MAG transcripts, at least at day 18 and be yond, appeared to be normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We surmise that the Northern blot analyses of Fujita et al [21] were insufficiently sensitive to detect both isoforms since they even failed to detect L-MAG in normal adult mice. It is also worth noting that Konat et al [2] have, by Northern blot analysis of mRNA for qk MAG, concluded that the processing of MAG transcripts, at least at day 18 and be yond, appeared to be normal.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable investigation has led to the characterization of many biochem ical, morphological and physiological fea tures of this mutant (studies prior to 1984 have been reviewed [1]. More recent investi gations of gene expression for specific myelin-related proteins have called attention to several aspects of anomalous neural devel opment and dysregulation in myelinogenesis [2][3][4], but the specific genetic target, known to be on chromosome 17, remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear pellet was subsequently homogenized in 5% citric acid and purified as described by Konat et al (1990).…”
Section: Isolation Of Nucleimentioning
confidence: 99%
“…In the plp gene, two splicing products named PLP and DM20 are produced by choosing different 5Ј splice sites of exon 3 (12). Although several studies of MBP and PLP expression in qk v mice have been reported, these experiments characterized the total gene expression, but not that of individual isoforms (19,20). Thus, it is still not clear whether their alternative splicing is disturbed in the mutant.…”
mentioning
confidence: 99%